(untitled) (Journal of Tikapur Multiple Campus, 2018)
Traffic flow is the study of the movement of individual drivers and vehicles between two points and the interactions they make with one another.Traffic flow models can be used to simulate traffic, for instance to evaluate ex-ante the use of a new part of the infrastructure. Models can be categorized based on, firstly, representation of the traffic flow in terms of flows (macroscopic), groups of drivers (macroscopic) or individual drivers (microscopic) and, secondly, underlying behavioral theory, which can be based on characteristics of the flow (macroscopic) or individual drivers (microscopic behavior). Microscopic traffic flow variables focus on individual drivers. Macroscopic traffic flow variables reflect the average state of the traffic flow. A macroscopic traffic flow model is a mathematical traffic model that formulates the relationships among traffic flow characteristics like density, flow, mean speed of a traffic stream etc. such models are conventionally arrived at by integrating microscopic traffic flow models and converting the single-entity level characteristics to comparable system level characteristics.